2013
DOI: 10.1007/s10067-013-2243-1
|View full text |Cite
|
Sign up to set email alerts
|

Regional migratory osteoporosis and transient osteoporosis of the hip: are they all the same?

Abstract: We hypothesized that regional migratory osteoporosis (RMO) and transient osteoporosis of the hip (TOH) terms describe a common disease process. Therefore, based on our patient, we aimed to review the pathogenesis, diagnosis, and treatment of both diseases. The patient was a pregnant woman in her third trimester with sacral insufficiency fracture, which was shortly followed by migratory arthralgia of both hips and ankles in a proximal to distal direction. She was operated (core decompression) for both hips and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 15 publications
0
18
0
2
Order By: Relevance
“…It is nowadays accepted that RMO constitutes a progression of TOH [13,15,16] with studies proposing a common pathophysiology between the two entities [17]. Cahir et al [15] have proposed that 72% of TOH patients progress to RMO during the first year after their diagnosis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is nowadays accepted that RMO constitutes a progression of TOH [13,15,16] with studies proposing a common pathophysiology between the two entities [17]. Cahir et al [15] have proposed that 72% of TOH patients progress to RMO during the first year after their diagnosis.…”
Section: Discussionmentioning
confidence: 98%
“…Several case reports and patient series describe TOH as a disease mostly affecting patients during the fourth decade of their life [2,3,12,13], with a male predominance and a predilection for left hips. Our results confirm the above data with an approximately 3:1 male:female ratio.…”
Section: Discussionmentioning
confidence: 99%
“…With insufficiency of intake calcium added to the scene, a negative balance is created and this may trigger TO. [15] Insufficient calcium intake was seen in our case, which increased risk factors for this disorder. [1,14] Transient osteoporosis can be recovered from spontaneously.…”
Section: Discussionmentioning
confidence: 49%
“…[1,14] Transient osteoporosis can be recovered from spontaneously. [15] It has also been reported that TO was improved by the termination of pregnancy in severe cases that do not respond to the other treatment. [16] Interestingly in our case, a remission was not seen during the postpartum period and migration occurred other joints.…”
Section: Discussionmentioning
confidence: 95%
“…The etiology of regional migratory osteoporosis is also unknown, although some authors have suggested that transient osteoporosis of the hip and regional migratory osteoporosis reflect the same underlying process. 106 …”
Section: Figure 12mentioning
confidence: 97%